2017
DOI: 10.1159/000484522
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up of Asymptomatic High-Risk Patients with Normal Cervical Length to Predict Recurrence of Preterm Birth

Abstract: Background: A midtrimester cervical length (CL) <25 mm is associated with spontaneous preterm birth (sPTB). However, as CL ≥25 mm is not enough to exclude recurrence in high-risk patients, follow-up CL measurement later in pregnancy has been proposed. Objectives: To evaluate whether CL measurement at 26±1 weeks in asymptomatic high-risk patients improves the prediction of sPTB recurrence. Methods: A retrospective cohort of high-risk women because of previous sPTB was analyzed. Patients with a CL ≥25 mm at 20±1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(36 reference statements)
2
1
1
Order By: Relevance
“…The use of a 25‐mm CL threshold, the same used for universal screening in the 18–24 week window, only identifies a small proportion of women who will deliver preterm. The screen‐positive rate for CL ≤ 25 mm in our cohort was 2.5% at 24 +0 –27 +6 weeks and 6.1 at 28 +0 –32 +0 weeks, which is similar to that reported on previous studies in asymptomatic singleton pregnancies that were screened at approximately 24–30 weeks of gestation 14,16–19 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The use of a 25‐mm CL threshold, the same used for universal screening in the 18–24 week window, only identifies a small proportion of women who will deliver preterm. The screen‐positive rate for CL ≤ 25 mm in our cohort was 2.5% at 24 +0 –27 +6 weeks and 6.1 at 28 +0 –32 +0 weeks, which is similar to that reported on previous studies in asymptomatic singleton pregnancies that were screened at approximately 24–30 weeks of gestation 14,16–19 …”
Section: Discussionsupporting
confidence: 89%
“…The screen-positive rate for CL ≤ 25 mm in our cohort was 2.5% at 24 +0 -27 +6 weeks and 6.1 at 28 +0 -32 +0 weeks, which is similar to that reported on previous studies in asymptomatic singleton pregnancies that were screened at approximately 24-30 weeks of gestation. 14,[16][17][18][19] The prevalence of sPTB in our population was low (1.9%), and is lower than those reported on previous studies (range 4.3%-12.5%). 5,16,17 The difference may be explained by the criteria used…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Performance of UCA and CL measurements with relation to preterm delivery and the time interval until delivery in patients with contractions was another issue addressed in our study and showed significance for gestational age, CL, and UCA. Recent studies confirmed the relationship between CL and duration of pregnancy for threatened abortions and recurrence in asymptomatic pregnancies 24,25 . Our study showed a correlation between CL and UCA with the duration of pregnancy for TPL; specifically, the shorter CL and the wider the UCA, the greater the risk for preterm delivery.…”
Section: Discussionsupporting
confidence: 87%